Catching up with the ‘core’: The nature of the agricultural machinery sector and challenges for Chinese manufacturers - SAFDAR, M. T. (Institutional Knowledge at Singapore Management University, 2019)
The current era of globalisation has been accompanied by China’s rise as a major economic actor. Chinese firms are expanding their presence globally and are seeking to ‘catch-up’ with firms in developed countries across different sectors. This paper uses China’s agricultural machinery sector as a vehicle to examine the challenges faced by firms from developing countries in their effort to catch-up with ‘core firms’. Chinese firms operating in the sector struggle to compete with a small number of dominant core firms based in developed countries. These core firms are sectoral leaders with a global presence. They are continuously strengthening their competitive advantage using diverse strategies, including: investing in R&D, focused acquisitions and developing relationships with actors internal and external to agriculture. The challenge of catching-up for Chinese firms in the sector has further increased as developed countries seek to protect firms in strategic sectors like agriculture. By examining the changing nature of the agricultural machinery sector, and the role of core firms, the paper highlights the substantial barriers facing Chinese firms in their efforts to catch-up. This paper has important implications, as it shows that even if firms from developing countries enjoy state-support, they will increasingly struggle to catch-up.